Ecomusicology: A socioecological dimension towards acoustically sustainable residential buildings - Peter Uchenna Okoye; Kevin Chuks Okolie; Christian Ifeanyi Ohaedeghasi; Chukwuemeka Ngwu (Center for Science and Technology, IAIN Surakarta, 2020)
This study examined the socioecological roles of music sounds towards achieving acoustically sustainable residential building. The study adopted a survey research approach where questionnaires were distributed to the occupants of different types of residential buildings in three urban cities of Anambra State Nigeria. The survey data were analysed using Statistical Package for the Social Science (SPSS) Software. The results revealed that music plays significant roles towards acoustically sustainable building performance with the overall average mean score index of 4.36 and a range of 3.64 to 4.87. But the three most outstanding roles played by music towards acoustically sustainable building performance were: Enabling pleasant sound environment (4.87), improving quality of relaxation and resting (4.83), and increasing acoustic comfort and satisfaction (4.79). The result of one-way ANOVA revealed that music sounds significantly influence acoustical sustainability performance of residential buildings (p-value (.000) < Î± (0.05); F-ratio (148.377) > F-critical (3.020)); and that there was no significance difference between opinions of residents of the three urban cities in this regard (p-value (0.713) > Î± (0.05); F-ratio (0.338) < F-critical (3.020)). This study therefore, canvassed for integration of music principles and acoustics into sustainable building design processes as a way of achieving a sustainable building.